Respuesta :
Answer:
10 x^2 + 8 x + 1
Step-by-step explanation:
Simplify the following:
8 x^2 + 2 x^2 + 7 x + x - 3 + 4
Grouping like terms, 8 x^2 + 2 x^2 + 7 x + x - 3 + 4 = (2 x^2 + 8 x^2) + (x + 7 x) + (4 - 3):
(2 x^2 + 8 x^2) + (x + 7 x) + (4 - 3)
2 x^2 + 8 x^2 = 10 x^2:
10 x^2 + (x + 7 x) + (4 - 3)
x + 7 x = 8 x:
10 x^2 + 8 x + (4 - 3)
4 - 3 = 1:
Answer: 10 x^2 + 8 x + 1
Answer:
[tex]10 {x}^{2} + 8x + 1[/tex]
Step-by-step explanation:
[tex]2 {x}^{2} + x + 4 -3 + 7x + 8 {x}^{2} \\ = 2 {x}^{2} + 8 {x}^{2} + x + 7x + 4 - 3 \\ = 10 {x}^{2} + 8x + 1[/tex]